Satisfaction of customers towards claims management process at Anika Insurance Brokers Sdn Bhd / Norhayati Abdullah - Abdullah, Norhayati (Faculty of Business and Management, 2010)
The title of this project paper is “Satisfaction of Customers towards Claims Management Process at Anika Insurance Brokers Sdn Bhd. The objective of this research is to identify level of customer satisfaction and also to rank factors that contribute to satisfaction of customers towards claims management process by Anika Insurance Brokers Sdn Bhd. Therefore, the research is done in order to identify several reasons that might cause the problem. The factors such as services, knowledge, commitment and efficiency are studied. The sample size of this study is 50 respondents. The data are analyzed by using Statistical Programme for Social Science (SPSS). The finding shows that majority of the respondents are satisfied with services provided by Anika Insurance Brokers Sdn Bhd especially in claims department. Thus, the researcher will recommend based on all of the variables.